Effects of Emotional Testimony and Gruesome Photographs on Mock Jurors' Decisions and Negative Emotions. Issue 1 (2nd January 2016) - Matsuo, Kayo; Itoh, Yuji
Abstract : The present study investigated the combined and individual effects of emotional testimony and gruesome photographs on mock jurors' verdict decisions and emotions. Participants ( n = 127) were provided with a murder trial transcript and then rendered verdicts in a 2 (emotional testimony: present, absent) × 2 (gruesome photographs: present, absent) between-groups design. They also rated their negative emotions before and after the transcript. The results indicated a combined effect of emotional testimony and gruesome photographs on verdict decisions: the emotional testimony alone had a significant effect on guilty verdicts while the gruesome photographs had only a marginally significant effect. Negative emotions were aroused by the emotional testimony when the gruesome photographs were not presented. The impact of emotional evidence on verdict decisions is discussed.